(untitled) (International Journal of Environmental Sciences, 2025)
Temsula Ao (1945–2022), the seminal Naga poet-ethnographer, cultivated a six-decade poetic corpus that transcends aesthetic expression to become a biocultural manifesto for indigenous sustainability. Through ecocritical analysis of her complete poetic oeuvre—Songs That Tell (1988), Songs That Try to Say (1992), Songs of Many Moods (1995), Songs from Here and There (2003), Songs from the Other Life (2007), and Songs along the Way Home (2017)—this research establishes Ao as a pioneering voice in decolonial ecopoetics. Her work documents the violent disintegration of human-nature reciprocity under extractive capitalism while preserving ancestral ecological knowledge as regenerative pathways. Her poetry demonstrates that cultural continuity is the bedrock of ecological resilience, positioning poetry as a vessel for biocultural preservation. Methodologically, this study employs frames of interdisciplinary ecocriticism, ecofeminism, and ethnopoetics to explore how Ao’s poetry becomes both elegy for ecological loss and blueprint for regenerative futures.